Radiographic Union Score for Tibia (RUST) scoring system in adult diaphyseal femoral fractures treated with intramedullary nailing: an assessment of interobserver and intraobserver reliability - Panchoo, Pravesh (Division of General Surgery, 2023)
Objectives The Radiographic Union Score for Tibia (RUST) scoring system has been validated in multiple studies assessing the healing of tibial fractures. Our objective was to assess the inter and intraobserver reliability for the RUST in diaphyseal femoral fractures treated with intramedullary (IM) nailing. Patients and Methods A total of 60 sets of anteroposterior (AP) and lateral radiographs of diaphyseal femoral fractures treated by reamed IM nailing were randomly selected from a prospectively collected database. The 60 sets of radiographs were then scored by three reviewers using the RUST system. Interobserver reliability was measured at initial scoring. The 60 sets of radiographs were scored again by the three reviewers to calculate the intraobserver reliability. Results The RUST scores ranged from 4 to 12 with a mean score of 11.3 ± 1.3. The interobserver intraclass correlation coefficient (ICC) was 0.87 (95% CI, 0.81-0.92) and the intraobserver ICC was 0.91 (95% CI, 0.88-0.94), which indicated excellent agreement. Conclusion This study demonstrated that the RUST system can be used reliably in the assessment of healing in diaphyseal femur fractures treated by reamed intramedullary nailing, with excellent interobserver and intraobserver reliability.